On Kolmogorov complexity and the costs of carrying out strategies (University of Oxford, 2000)
It is common to model costs of carrying out strategies in games in relation to the complexity, in some sense, of the strategies. We show a particularly general definition of complexity for this purpose, one that subsumes many alternatives as special cases. We explore how this definition can be used and developed, and illustrate with applications to the analysis of two player finite repeated games.